의학교육에서의 행복 관련 교육과정 도입을 위한 탐색적 연구 - 유효현(Hyo Hyun Yoo) (한국콘텐츠학회 논문지, 17(3), 2017)
The purpose of this research was analyzing pre-post change of concept recognition structure about happiness and activity in which medical school students feel happiness, in order to develop such curriculum accordingly. Research subjects included a total of 36 sophomores attending medical school, and a day reconstruction method and network analysis were applied. According to the research finding, while medical school students were experiencing a lot of happiness while eating/talking and doing leisure activities, the frequency of feeling happiness through learning activities was shown to be low. Words that expressed happiness before and after were similar in many parts and 'economy' showed the highest degree centrality before and 'work' showed the highest degree centrality after. Because the structure of the concept about happiness was divided from 1 group into 4 groups including one's work, positive self, health of family, value about life etc., perception of the concept about happiness was changed from the concept about superficial happiness to the concept about actual happiness. Therefore, in order for prospective doctors who will treat human health to establish the concept and value about happiness properly, education about happiness is necessary and for this, curriculum related to happiness must be developed systematically. 본 연구의 목적은 의학교육에서의 행복과 관련된 교육과정 도입을 탐색하기 위하여 의학전문대학원생들이 행복을 느끼는 활동 및 행복에 대한 개념 인식구조의 사전-사후변화를 분석하였다. 연구대상은 의학전문대학원에 재학 중인 2학년 학생 총 36명이었고, 일상재구성법과 네트워크분석을 사용하였다. 연구결과, 의학전문대학원생들은 먹기/대화하기, 여가활동을 하면서 행복을 많이 경험하고 있는 반면 학습활동을 통한 행복을 느끼는 빈도는 낮게 나타났다. 사전-사후의 행복을 표현하는 단어들은 많은 부분 유사하였고, 사전에는 '경제', 사후에는 '일'이 가장 높은 연결정도중심성을 나타냈다. 행복에 대한 개념의 구조가 1개 그룹에서 자신의 일, 가족의 건강, 삶에 대한 가치, 긍정적인 자아 등의 4개 그룹으로 나누어져 행복에 대한 개념이 피상적인 행복에 대한 개념에서 실제적인 행복에 대한 개념으로 인식이 변화하였다. 따라서 인간의 건강을 다룰 예비의사들이 행복에 대한 개념과 가치 등을 바르게 정립할 수 있도록 행복에 대한 의도적인 교육이 도입되어야 하고, 이를 위해서 행복과 관련된 교육과정이 체계적으로 개발되어야 할 것이다.